2018
DOI: 10.3892/etm.2018.6916
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the severity of chronic kidney disease with serum inflammation, osteoporosis and vitamin D deficiency

Abstract: Correlation of the severity of chronic kidney disease (CKD) with serum inflammation, osteoporosis and vitamin D deficiency was investigated. A total of 78 patients suffering from CKD who presented to the Union Hospital from December 2015 to December 2017 were selected randomly and divided into three groups based on the severity of the disease. Comparisons of interleukin-6 (IL-6), C-reactive protein (CRP), tumor necrosis factor-α (TNF-α), indicators of osteoporosis [serum phosphate, serum calcium and bone miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Nevertheless, the severity of CKD is strongly associated with inflammatory mediators and insufficiency of vitamin D. With the progression of CKD, more inflammatory factors are released, phosphate levels increase, and calcium levels decrease. Increased phosphate level activates the NF-κB pathway and leads to an increased level of tumor necrosis factor-alpha (TNF-α), thus causing overactivation of the inflammatory system [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the severity of CKD is strongly associated with inflammatory mediators and insufficiency of vitamin D. With the progression of CKD, more inflammatory factors are released, phosphate levels increase, and calcium levels decrease. Increased phosphate level activates the NF-κB pathway and leads to an increased level of tumor necrosis factor-alpha (TNF-α), thus causing overactivation of the inflammatory system [23].…”
Section: Methodsmentioning
confidence: 99%
“…PTH is a crucial representative biomarker for bone fragility [23]. It usually remains normal until GFR is 45 mL/minute/1.73 m 2 , and its elevation reduces GFR [12,24,25].…”
Section: Methodsmentioning
confidence: 99%
“…A vitamin D deficiency is a common condition associated with kidney disease. Many clinical studies have highlighted how a vitamin D deficiency is an important risk factor for CKD patients [36, 37].…”
Section: Resultsmentioning
confidence: 99%
“…53 The changes place both genders at risk and have been postulated to lead to severe adverse consequences such as osteoporosis, breast, colon and prostate cancers and hypertension. 53 Chronic kidney disease equally places both genders at increased risk of osteoporosis and increased requirement for vitamin D. 54 Clinical trials have demonstrated that 800 IU (20 μg) per day of vitamin D in combination with 1 200 mg calcium reduced the risk of fractures due to falls in the institutionalised elderly, who are not ambulatory or exercising, and that single doses of 100 000 IU orally every fourth month, without calcium, reduces fracture risk in mobile community-dwelling individuals over 65 years of age. 53 Another study suggested a three-year combined programme of denosumab (a monoclonal antibody) and vitamin D supplementation for the treatment of osteoporosis and rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%